2020
DOI: 10.1177/1120672120984408
|View full text |Cite|
|
Sign up to set email alerts
|

Acute monocular oligemia in a patient with migraine with aura demonstrated using OCT-angiography: A case report

Abstract: Introduction: Migraine is one of the most common causes of transient visual loss. Optical coherence tomography angiography (OCTA) provides fast and non-invasive imaging of the retinal vessels. We report the first case of monocular retinal oligemia demonstrated using OCTA during a migraine attack with aura. Case description: A 27-year-old man with a previous history of migraine with visual aura was seen in the emergency room due to acute left hemicranial pain with positive visual symptoms in his right eye. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…There have also been two case reports that have showed reduction of ocular vascularity and VAD during a migraine attack. 61,63 Both these case studies looked at transient changes during an attack in a single individual participant; however, the observations in these case reports are in line with the reduction of perfusion that we find in our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There have also been two case reports that have showed reduction of ocular vascularity and VAD during a migraine attack. 61,63 Both these case studies looked at transient changes during an attack in a single individual participant; however, the observations in these case reports are in line with the reduction of perfusion that we find in our study.…”
Section: Discussionsupporting
confidence: 88%
“…The difference between these results and ours could be due to multiple differences in study design including evaluation of a MO group only, no interictal baseline scan, the use of 6 × 6‐mm scans, which may have lower resolution, as well as not using the VFI measure, which is thought to be more sensitive to perfusion differences. There have also been two case reports that have showed reduction of ocular vascularity and VAD during a migraine attack 61,63 . Both these case studies looked at transient changes during an attack in a single individual participant; however, the observations in these case reports are in line with the reduction of perfusion that we find in our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Aura migraineurs had decreased deep foveal VD ipsilateral to headache during prodromal aura, improving 3 hours post-aura ( Kızıltunç and Atilla, 2020 ). In one study, investigators found that aura migraineurs had right-eye macular hypoperfusion during the right aura but left hemicranial pain, resolving within a week after resolution of pain and aura ( González-Martín-Moro et al, 2023 ). Aura migraineurs had thinner maculae after 6 months post-attack ( Cunha et al, 2008 ).…”
Section: Retinamentioning
confidence: 99%
“…I read with great interest the case report by González-Martín-Moro et al 1 which described monocular superficial plexus oligemia detected using OCTA in a patient with migraine with aura. The authors hypothesised that this oligemia was likely secondary to primary retinal spreading depression phenomena.…”
mentioning
confidence: 98%